Integration of CSR and SDG in creating added value of the textile industry - Vićentijević Kosana; Rakić Snežana; Marković Vesna (Tekstilna industrija, 2022)
Socially responsible business entities (CSR) have reoriented their CSR initiatives towards environmental and social management. The Sustainable Development Goals (SDGs) are newer strategic tools that focus on addressing sustainability issues arising from increased production, consumption and disposal. Sustainability will be the most important directive in the near future, therefore, this paper aims to examine the cohesiveness between current CSR initiatives in the fashion and textile sector and the prescribed SDGs. The paper further highlights a case study of good practice of a clothing factory in the Republic of Serbia, which incorporates CSR and SDG above the prescribed regulations. The conclusions in this paper suggest several future research directions.